Influence of family cohesion on Chinese adolescents’ engagement in school bullying: A moderated mediation model - Chen, Xin; Jiang, Jiarui; Li, Zuoshan; Gong, Yue; Du, Jiangli (Frontiers in Psychology, 2022)
In this study, a total number of 1,026 chinese adolescents were surveyed using the cohesion sub-scale of the Family Environment Scale, the Self-control Scale, the Parental Monitoring Questionnaire, and the revised Olweus Bully/Victim Questionnaire to explore the effects of family cohesion on adolescents’ engagement in school bullying and the mechanisms of self-control and parental monitoring in the relationship between them. The results showed that: (1) family cohesion, self-control, and parental monitoring were significantly and negatively related to school bullying; (2) family cohesion directly influenced school bullying and also indirectly influenced school bullying through a mediating effect – self-control; (3) parental monitoring played a moderating role in the path of self-control affecting school bullying. Therefore, to reduce the occurrence of school bullying, it is necessary to strengthen the self-control ability of adolescents and improve the family cohesion environment and maintain a moderate level of parental monitoring. The results of this study revealed the effect of family cohesion on adolescents’ engagement in school bullying and its mechanism of action, which can provide a theoretical basis for preventing and reducing the occurrence of school bullying incidents.